Japan’s Peacekeeping at a Crossroads by Hiromi Nagata, Fujishige, Yuji Uesugi and Tomoaki Honda - Muhammad Rayyan Faisal (NUST Journal of International Peace and Stability)
Japan’s Peacekeeping at a Crossroads examines Japan’s evolving peacekeeping doctrine within its unique anti-militarist framework. The book traces Japan’s engagement in United Nations Peacekeeping Operations (UNPKOs), highlighting its historical constraints, legal complexities, and public opposition to military deployment. The review commends the book’s structured analysis, detailing Japan’s transition from financial contributions to active troop deployment and its subsequent withdrawal from South Sudan in 2017. The authors argue that Japan’s reluctance aligns with broader Global North trends but overlook Japan’s distinctive domestic factors. While the book’s language is accessible, certain word choices introduce casualness, and its discussion of Global North-South troop contributions risks generalization. Despite these limitations, the book provides valuable insights into Japan’s peacekeeping policy, balancing international expectations with domestic constraints, and opens avenues for further research on Japan’s anti-militarist stance and developed states’ limited troop contributions to UNPKOs.